New Estimates for the Shadow Economies All over the World - Schneider, Friedrich; Buehn, Andreas; Montenegro, Claudio E. (2012)
This paper presents estimations of the shadow economies for 162 countries, including developing, Eastern European, Central Asian, and high income OECD countries over 1999 to 2006/2007. According to our estimations, the weighted average size of the shadow economy (as a percentage of 'official' GDP) in Sub-Saharan Africa is 37.6%, in Europe and Central Asia (mostly transition countries) 36.4% and in high income OECD countries 13.4%. We find that an increased burden of taxation (direct and indirect ones), combined with (labour market) regulations and the quality of public goods and services as well as the state of the 'official' economy are the driving forces of the shadow economy.